EFFECTS OF A CHINESE MEDICINAL PLANT RADIX ASTRAGALI ON THE OVARIECTOMIZED FEMALE RATS - Zheng, Yan; Jin, Yue; Zhu, Hai-Bin; Xu, Shao-Ting; Xia, Ya-Xian; Huang, Yue (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Perimenopausal syndrome occurs during the transition to menopause. Complementary and alternative medicine, especially Chinese medicinal plants, has manifested significant effects in alleviating perimenopausal symptoms. However, little research has been focused on the effects of Chinese medicinal plant on the immune function of the perimenopausal women. The present study aimed to explore the effects of Radix Astragali (RA) on the sex hormone levels and the interleukins of the ovariectomized female rats. 24 female Sprague-Dawley (SD) rats were randomly divided into model control group (MOD group), sham-operation group (SHAM group), RA group and estrogen group (EST group). After all the treatment ended, the serum levels of estradiol (E2), follicle stimulating hormone (FSH), luteinizing hormone (LH), interleukin-2 (IL-2), and interleukin-8 (IL-8) were measured using enzyme-linked immune-sorbent assay (ELISA) and the uterus was removed and weighed after blood exsanguinations immediately. In the MOD group, the serum levels of E2 were significantly lower, and the serum levels of FSH and LH were markedly higher than those of the RA group, EST group and SHAM group (P<0.05). In the RA group, the serum levels of E2 were significantly lower, and the serum levels of FSH were markedly higher than those of the SHAM group and EST group, respectively. In the MOD group, the serum levels of IL-2 and IL-8 were significantly lower than those of the RA group, EST group and SHAM group (P<0.05), and no marked differences existed among RA group, EST group and SHAM group in the serum levels of IL-2 and IL-8 (P>0.05). The uterine weight of the rats in the RA group, EST group and SHAM group were significantly higher than those of the rats in MOD group (P<0.05). There were no marked differences among the rats from RA group, EST group and SHAM group on the uterine weight (P>0.05). It is concluded that RA can significantly improve the immune functions of the ovariectomized female rats, although it cannot change the sex hormones levels as significantly as estrogen.